The Substance of Representation - John S. Lapinski (Princeton University Press, 2013)
IN WRITING THIS BOOK, I often thought about Sisyphus. In Greek mythology, he was the king who was punished by being forced to roll an immense boulder up a hill only to watch it roll back down. My metaphorical boulder involved collecting more data and creating better measures of lawmaking. Fortunately, I was not compelled to repeat this action forever (though it felt like it). Of course, I didnâ€™t make those trips up the hill alone. Many people helped me in this effort. Intellectually, the project began while I was a graduate student Columbia University. I wrote a paper for a graduate seminar taught by Ira Katznelson dealing with conceptual issues related to policy substance, the study of Congress, and American political development. Ira was already my dissertation chair at the time (along with Nolan McCarty, who was co-chair), but the paper was a â€œcritical juncture,â€ as it led to a series of collaborations. Those collaborative projects have been instrumental to this book. Specifically, the coding schema in this book is based on our joint work. In addition to being a terrific co-author, Ira has influenced my own work in more ways than seem possible. His intellect and work ethic make him a truly inspiring individual. I owe him a great debt. Many others deserve credit in the making of this book. Josh Clinton, a frequent co-author, was instrumental in turning my earlier work on measuring legislative significance into much more refined and sophisticated work. The legislative significance measure presented in chapter 4 is based on our collaborative efforts. He is clearly a partner in this project. There are others who also provided much good counsel. One of those individuals is David Mayhew. I had the good fortune to develop a relationship with David during my stint at Yale University. He is a scholar who provides inspiration and much good advice. His social science instincts are unparalleled, and his advice was instrumental for many of the concepts in this book.